Agriculture and Rural Development Day 2011 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
In connection to the UNFCC COP 17 conference in Durban, South Africa in December 2011, CCAFS and several other partners organized an Agriculture and Rural Development Day (ARDD). It was a major one-day event that brought together several hundred policy makers, farmers, scientists and development experts to discuss the urgent need for rural people in developing countries to play a greater role and receive stronger support in climate change adaptation and mitigation.